The Nineteenth-Century Anglo-Indian Opium Trade to China and its Lasting Legacy (2021)
In recent years, two apparently different and unconnected problems have received repeated attention from global news outlets, namely the opioid crisis and the pro-democracy movement in Hong Kong. The opioid crisis, which is especially catastrophic in the United States, involves the over-prescription and abuse of synthetic opioid painkillers such as oxycontin and fentanyl (Felter, 2020). The pro-democracy movement in Hong Kong involves legions of pro-testers, many of them university students, taking to the streets against what they see as the erosion of their civil liberties at the hands of the mainland Chinese government (Perper, 2019). How can these two issues possibly be connected? This paper tells the story of how the world’s first great opioid crisis occurred in nineteenth-century China, and how the drug trafficking British thwarted the Chinese government’s attempts to stop drug imports, fighting two wars in the process. Upon conclusion of the first of these wars, China was forced to cede the territory of Hong Kong. This British colonial outpost became the principle entrepôt for British opium entering the Chinese market. Over the next century and a half, Hong Kong grew into one of the world’s most dynamic commercial cities, and its citizens enjoyed liberties under British rule that were not available to the mainland Chinese population. Thus, the legacy of the opium wars and the British opium trade to China is still very much with us today.